QUANTIFYING LEAD EXPOSURE TO PERSONNEL ON FORT RILEY RANGES - McKenna, Benjamin (My University, 2014)
Fort Riley Kansas is a U.S. Army military installation. In 2012 over five and a half million rounds of ammunition were fired on the training ranges (2). Most of these munitions contain lead and over time lead will accumulate on the ranges. Inhaled or ingested lead can have detrimental effects on human health. This study was conducted to determine if soldiers and range personnel are being exposed to lead particulates and if so, what are the levels of lead at the different locations. Soil, air and dust samples were collected from the ranges where personnel spend their work day and tested for the presence of lead. Many of the samples collected tested positive for lead in the areas one would expect to find lead particulates to be present on a shooting range. Soil samples collected from outside the range area showed that lead particulates are not being carried off the ranges into the surrounding training areas. However, there was a sample collected from a small arms range ammunition shed that tested positive for lead when it shouldn’t have considering the low number of ammunition fired on that range compared to other ranges ammunition sheds that tested negative for lead. This positive test resulted in multiple follow ups with different departments on Fort Riley to determine the cause of the contamination and what changes were needed. It was determined that the ammunition shed on the small arms range most likely contained lead particles because of a misunderstanding of policy by the soldiers using the range; soldiers being briefed on the proper turn-in procedures for spent ammunition casings could alleviate the lead contamination issue on this range. Reviewing current procedures in place to protect range maintenance personnel from lead exposure only raised more questions in the effectiveness of these procedures; the Fort Riley Public Health/Industrial Hygiene department will be conducting further studies to determine these risks.
Keywords: Fort Riley; Lead exposure; Ammunition lead; Public Health (0573)